Customers satisfaction and service quality of Islamic Banks in Perak, Malaysia - Nor Azrin Md Latip (Tanjong Malim, 2019)
Customers satisfaction and service quality of Islamic Banks in Perak, Malaysia by Nor Azrin Md Latip